Zukunft der Werkstätten Perspektiven für und von Menschen mit Behinderung zwischen Teilhabe-Auftrag und Mindestlohn - Schachler, Viviane; Schlummer, Werner; Weber, Roland (Verlag Julius Klinkhardt, 2023)
The book "Zukunft der Werkstätten" (Future of Workshops) deals with the future and perspectives of workshops for people with disabilities (WfbM). In today's field of tension of inclusion, the workshops are subjected to a critical examination. The book takes up this necessary discussion from different perspectives and links it with aspects of the more than 70-year history and the necessary development needs of the workshops. It describes the basics as well as current discussion processes on participation and inclusion in the context of workshops. Through the critical and reflective presentation of various aspects, the book offers differentiating suggestions.